Examples of determining the rank of a number represented in the non-position system of residual classes - Krasnobayev, V.A.; Zamula, A.A.; Yanko, A.S. (Radiotekhnika, 2018)
Possible methods are considered for determining the positional feature of the non-position code (PFNC) of the number system in residual classes (SRC) of the rank of a number. Two methods for determining the rank of a number in a SRC are presented. The main attention is paid to the method of determining the rank of a number based on using the result of the proof of the theorem on the rank of the sum of two numbers. Examples of a specific definition of the rank of a number are given.